Analysis of Location Determination Using Wireless Signals at Low Range Using Third Order Polynomial Regression - Sutiyo; Yogi Yudo (FKOM UNIKU, 2026)
At short range, Location Determination Using Wireless Signals is considered a quite challenging problem. This paper discusses Location Determination Using Wireless Signals at short range with a Polynomial approach. The combination of retained independent effect of each component measure from Polynomial Regression and positioning in wireless fingerprinting produces a Polynomial that can provide good results for Location Determination Using Wireless Signals at short range. The measurement was conducted at Samas Beach Road, Yogyakarta, within a 0–100-meter range divided into 11 measurement points spaced every 10 meters. Validation results indicated that the third-order polynomial regression achieved a determination coefficient (R²) of 0.9982, confirming its high accuracy in representing the measured signal strength variations at short range